The Construction of Legitimacy through Illocutionary Speech Acts in the Indonesian President’s Address at the 2026 World Economic Forum - Yasir Mubarok; Sugiyo; Zaki Zainal Arifin (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2026)
Purpose This study aimed to reveal the types and distribution of illocutionary speech acts and their role in building the legitimacy of Indonesian leadership and economic policies in the speech of the RI President at the World Economic Forum (WEF) Davos 2026 entitled President Prabowo's Concept of Economic Thought Method This research employed a qualitative approach using a descriptive-analytical design. The data were obtained from the official video recording of the speech observed and transcribed verbatim. The analysis combined Searle’s (1979) theory of illocutionary speech acts and van Leeuwen’s (2007) legitimacy framework. Results/findings The study found 272 illocutionary speech acts to express different purposes, namely representatives used to convey facts and claims of success, commissive used to show promises or commitments, expressive functioned to express appreciation or pride, directives used to invite or encourage the audience. The legitimacy pattern in this speech used strategies according to van Leeuwen (2007), especially rationalization, moral evaluation, and authorization, as well as a little mythopoesis. Conclusion The study concluded that the WEF Davos 2026 speech operates as a strategic diplomatic instrument that conveys information, constructs legitimacy, and reinforces Indonesia’s position in global political-economic communication. It recommends further research on international political speeches to deepen understanding of how speech acts and legitimacy strategies shape global diplomatic narratives.